Absence of Exogenous Glucose in the Perfusate During Kidney Hypothermic Machine Perfusion Does Not Affect Mitochondrial Function - Dafni Efraimoglou; L. Annick van Furth; Albert Gerding; Barbara M. Bakker; Jan-Luuk Hillebrands; Henri G. D. Leuvenink; Leonie H. Venema (Transplantology, 2025)
Background: Optimizing organ preservation techniques is imperative in the face of donor kidney shortage and high waiting list mortality. Hypothermic machine perfusion (HMP) has emerged as an effective method to improve graft function post-transplantation, particularly for deceased donor kidneys, prone to ischemia reperfusion injury (IRI). The perfusion solution includes glucose to support kidney metabolism; however, its effect on mitochondrial function remains unclear. The present study investigated the effect of glucose supplementation during 24 h of oxygenated HMP on mitochondrial function in porcine kidneys. Methods: After 30 min of warm ischemia, porcine slaughterhouse kidneys were preserved for 24 h using HMP with one of the following three solutions: the standard HMP preservation solution, University of Wisconsin machine perfusion (UW-MP) solution, which contains glucose; the solution used for static cold storage, University of Wisconsin cold storage (UW-CS) solution, which lacks glucose; or the UW-CS supplemented with 10 mmol/L glucose. Tissue and perfusate samples were collected before, during, and after perfusion for further analysis. Results: ATP production, mitochondrial respiration, and oxidative stress markers were not significantly different between groups. Glucose was released into the perfusion solution even from kidneys without exogenous glucose supplementation in the perfusate. Conclusions: These results suggest that kidney mitochondrial respiration does not depend on the presence of glucose in the HMP perfusion solution at the start of perfusion, underscoring the need for further exploration of nutrient supplementation and mitochondrial function in organ preservation strategies.